2014
DOI: 10.1371/journal.pone.0111840
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Anti-Tumor Activity of EZH2 Inhibitors and Glucocorticoid Receptor Agonists in Models of Germinal Center Non-Hodgkin Lymphomas

Abstract: Patients with non-Hodgkin lymphoma (NHL) are treated today with a cocktail of drugs referred to as CHOP (Cyclophosphamide, Hydroxyldaunorubicin, Oncovin, and Prednisone). Subsets of patients with NHL of germinal center origin bear oncogenic mutations in the EZH2 histone methyltransferase. Clinical testing of the EZH2 inhibitor EPZ-6438 has recently begun in patients. We report here that combining EPZ-6438 with CHOP in preclinical cell culture and mouse models results in dramatic synergy for cell killing in EZH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 41 publications
1
50
0
Order By: Relevance
“…These findings suggest that wild-type EZH2 lymphomas have additional active pathways that support their growth and survival. A previous study has demonstrated a synergistic relationship between tazemetostat and glucocorticoids in both wild-type and mutant EZH2 DLBCL cell lines (26). We present here that in addition to glucocorticoids, agents that selectively target the B-cell receptor pathway, ibrutinib (BTKi) and tamatinib (SYKi) also have a synergistic relationship with tazemetostat.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…These findings suggest that wild-type EZH2 lymphomas have additional active pathways that support their growth and survival. A previous study has demonstrated a synergistic relationship between tazemetostat and glucocorticoids in both wild-type and mutant EZH2 DLBCL cell lines (26). We present here that in addition to glucocorticoids, agents that selectively target the B-cell receptor pathway, ibrutinib (BTKi) and tamatinib (SYKi) also have a synergistic relationship with tazemetostat.…”
Section: Discussionmentioning
confidence: 56%
“…Tazemetostat was previously shown to have a synergistic relationship with glucocorticoid receptor agonists (GRAG) in cotreatment models of DLBCL (26). This work showed that cell lines with wild-type EZH2 were sensitive to the tazemetostat/GRAG combination, while only showing modest effects with single-agent tazemetostat.…”
Section: Introductionmentioning
confidence: 91%
“…4A, B) are strikingly different from those reported by Cao et al, in which omission of WDR5 has essentially no effect on the SET1A activity, while the MLL1 activity is nearly completely eliminated. 43 With regard to the points just discussed, it is worth noting the recent spate of successes in developing potent, SETtargeted, SAM-competitive inhibitors of EZH2 [56][57][58][59][60][61][62] and to also note that the MLL/SET1 family presents a number of features that parallel those of the EZHs. First, despite one group's catalysis of a gene repressive modification (EZH, H3K27 methylation) and the others catalysis of an activating one (MLL/ SET1, H3K4 methylation), the two groups share the same branch of the KMT phylogeny tree.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is an analogue of GSK126, it is less selective for EZH1 [105,109] . Remarkably, EPZ-6438 is recently going through clinical testing for Non-Hodgkin Lymphomas patients [110] .…”
Section: Sam Analoguesmentioning
confidence: 99%
“…Standard Non-Hodgkin Lymphoma therapy is a combination of several drugs, called CHOP (Cyclophosphamide, Hydroxyldaunorubicin, Oncovin, and Prednisone). Studies in vitro and in vivo demonstrated that the combination of EPZ-6438 with CHOP increases anti-proliferative benefits compared to treatment with the EZH2 inhibitor alone, and this effect is thought to be mediated by glucocorticoid receptor agonists such as Prednisolone, the active metabolite of Prednisone [110] . Moreover, other studies investigated the inhibition of EZH2 in combination with conventional therapies in prostate cancer.…”
Section: Combination Of Ezh2 Inhibitor With Other Drugsmentioning
confidence: 99%